Numerical simulation of storm surge envelopes associated with the recent severe cyclones impinging on the east and west coasts of India (MAUSAM, 1983)
Envelopes of storm surges generated by the Porbandar cyclone of 1975, Andhra Pradesh cyclone of 1977 and Pamban cyclone of 1978 are simulated on the computer. The locations and the magnitudes of peak storm surges are found to be in good agreement with observations.